ANALISIS BERITA PENYELESAIAN GANTI RUGI KORBAN LUMPUR LAPINDO - Dessy Trisilowaty (REFORMASI, 2012)
The problem posed in this research is the dominant theme in the news about the compensation for the victims of Lapindo mud disaster in two newspapers, Jawa Pos and Surya. This research is aimed at identifying the dominant theme in the news about the compensation for the victims of Lapindo mud disaster in two newspapers, Surya and Jawa Pos for a period of one month before and after a set date, that is 14 September 2007.This research applies the content analysis method because the object of the analysis is the messages in the news related to the disbursement of compensation for the victims of Lapindo mud disaster. The data shows that from August until 13 September 2007, the news in Jawa Pos was dominated by politics and government issues and the Surya daily, the most dominant theme is legal matters. For the news after the set date 14 September 2007 until October, the Jawa Pos reported the news is dominated by legal matters. As for the Surya daily, from 14 September 2007 until October 2007, legal matter was still dominant.